BIM Implementation in Asia Towards Functionalities: A Systematic Review - ‘Ariff Putra Ansaruddin Agus, Muhammad; Hamzah, Noraini; Azry Khoiry, Muhamad (International Journal of Engineering and Technology, 2019)
Building Information Modelling (BIM) becomes the important tools for architectural, engineering and construction (AEC) firms. BIM has been regarded as one of the growing requirements in the construction industry, as BIM provides a variety of facilities to assist in the smooth running of the project. The implementation of BIM in the construction industry has been identified by the researchers to determine the functionalities itself. Even though BIM has been implemented since decades ago, not all of the countries adopted BIM fully. This will influence the level of maturity of BIM for these countries. As Malaysia moves towards a vision of a high-income economy target, BIM provides the influence of information technology in the construction sector and the implementation of BIM leads to successful construction. This paper presents BIM implementation in several developed countries in Asia, as well as the functional issues of BIM will be highlighted. A systematic review of 42 journals and publications focusing on BIM functionalities in Asian region has been conducted and discussed. The finding shows publications about the functionalities of BIM in Asia have been growing rapidly. This paper is part of ongoing research into preparing a level of maturity for the Malaysian construction industry and its prediction.Â Â Â